MORAL OR ETHICAL CONCEPT OF CITIZENSHIP AND STATEHOOD IN ISLAM IN ISLAMIC RELIGIOUS EDUCATION LEARNING IN HIGHER EDUCATION - Yusuf, Yoseph Salmon (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2025)
This study aims to examine the concept of morality or ethics of nation and state in Islam and its implementation in Islamic Religious Education (PAI) learning in higher education. The concept of morality of nation and state in Islam is based on the basic values ​​of Islamic teachings such as justice (al-‘adl), trustworthiness, deliberation (shūrā), equality, tolerance, and social responsibility oriented towards the welfare of the people and the integrity of the state. This study uses a qualitative method with a literature study approach and descriptive-analytical analysis of primary and secondary sources in the form of the Qur'an, hadith, fiqh siyasah literature, as well as curriculum documents and PAI learning practices in higher education. The results of the study indicate that PAI learning in higher education has a strategic role in transforming Islamic moral values ​​into the context of national and state life through strengthening material on religious moderation, integration of national values, and the use of dialogical and reflective learning methods.